Exploring cariprazine as a treatment option for varied depression symptom clusters - Pejušković, Bojana; Munjiza Jovanović, Ana; Pešić, Danilo (Frontiers in Psychiatry, 2024)
Major depressive disorder (MDD) is among the most prevalent psychiatric conditions and a leading cause of disability worldwide. MDD presents a diverse range of symptoms that significantly impact personal, societal, and economic dimensions. Despite the availability of numerous antidepressant treatments (ADTs) targeting different molecular mechanisms, a substantial proportion of patients experience inadequate response, presenting a considerable challenge in MDD management. As a result, adjunctive strategies, particularly involving atypical antipsychotics, are often employed to enhance treatment efficacy. Cariprazine, a D2/D3 partial agonist, is distinguished from other atypical antipsychotics by its selective action on the D3 receptor and its modulation of 5-HT1A, 5-HT2A, and alpha 1B receptors. This distinctive pharmacological profile warrants investigation into its potential effectiveness and tolerability across various symptom domains of MDD, including pleasure, interest, and motivation; mood and suicidality; sleep and appetite; fatigue; psychomotor activity and anxiety; and cognitive function. Preliminary evidence from animal studies and clinical trials suggests that cariprazine may improve motivation, anhedonia, and cognitive function symptoms. Cariprazine shows promise in alleviating mood-related symptoms, though its impact on anxiety and its effects on agitation and psychomotor retardation remains uncertain. Cariprazine may be particularly beneficial for patients with MDD exhibiting anhedonia, cognitive deficits, and possibly fatigue and hypersomnia. Evaluating cariprazine’s efficacy across these symptom domains could reveal patterns that support more personalized treatment approaches for depression. Further research is essential to elucidate the role of cariprazine as an adjunctive therapy for adults with major depressive disorder who have an inadequate response to antidepressant monotherapy.